Role of Metazoan Mediator Proteins in Interferon-Responsive Transcription - Lau, Joe F. (American Society for Microbiology, 2003)
The interferon (IFN)-induced signal transduction and transcription activation complex, ISGF3, is assembled from three proteins, STAT1, STAT2, and IRF9. Of these components, STAT2 provides a fundamental and essential transcriptional activation function for ISGF3. In the present study, we show that ISGF3-mediated transcription is dependent on STAT2 interactions with DRIP150, a subunit of the multimeric Mediator coactivator complex. Other Mediator subunits, DRIP77 and DRIP130, were found either to bind STAT2 without augmenting ISGF3 transcriptional activity or to enhance ISGF3 transcription without binding STAT2, but only DRIP150 both enhanced IFN-dependent transcription and coimmunoprecipitated with STAT2. Endogenous DRIP150 and STAT2 were able to interact in solution, and DNA affinity chromatography and chromatin immunoprecipitation assays demonstrated that DRIP150 binds to the mature, activated ISGF3-DNA complex and is recruited to target gene promoters in an IFN-dependent fashion. IFN-dependent recruitment of DRIP130 to an ISGF3 target promoter and SRB10-STAT2 coprecipitation suggest indirect association with a multisubunit Mediator complex. The site of STAT2 interaction was mapped to DRIP150 residues 188 to 566, which are necessary and sufficient for interaction with STAT2. Expression of this DRIP150 fragment, but not DRIP150 fragments outside the STAT2 interaction region, suppressed ISGF3-mediated transcriptional activity in a dominant-negative fashion, suggesting a direct functional role of this domain in mediating STAT2-DRIP150 interactions. These findings indicate that the IFN-activated ISGF3 transcription factor regulates transcription through contact with DRIP150 and implicate the Mediator coactivator complex in IFN-activated gene regulation.